The Influence of Seasons and Weather on the Volume of Trauma Patients: 4 Years of Experience at a Single Regional Trauma Center - Se Heon Kim; Young Hoon Sul; Jin Young Lee; Joong Suck Kim (Journal of Trauma and Injury)
Purpose The purpose of this study was to determine the influence of seasons and weather on the volume of trauma patients in central Korea. Methods The records of 4,665 patients treated at Chungbuk National Hospital Regional Trauma Center from January 2016 to December 2019 were retrospectively reviewed. Meteorological data including hourly temperature (°C), precipitation (mm), humidity (%), and wind speed (m/s) for each district were collected retrospectively. Statistical analysis was done using the independent t-test, one-way analysis of variance (ANOVA), and linear regression analysis. Results Patients’ average age was 53.66 years, with a significant difference between men (49.92 years) and women (60.48 years) (p<0.001). Rolling/slipping down was a prominent cause of injury in winter (28.4%, n=283), with statistical significance (p<0.001). Trauma occurred least frequently in winter (p=0.005). Linear regression analysis revealed an increasing number of patients as the temperature increased (p<0.05), the humidity increased (p<0.001), and the wind speed decreased (p<0.001). Precipitation did not affect patient volume (p=0.562). One-way ANOVA revealed a decreased incidence of trauma when the temperature exceeded 30°C (p<0.001), and when the humidity was more than 75%, compared to 25–50% and 50–75%. Conclusions At the regional trauma center of Chungbuk National University Hospital, in central Korea, the number of trauma patients was lowest in winter, and patient volume was affected by temperature, humidity, and wind speed.